Impacto das tecnologias de informação e comunicação: cultura digital e mudanças sócio-culturais - Jorente, Maria José Vicentini [UNESP] (My University, 2012)
The contemporaneous culture presents new con ditions of interaction with the information flows in the knowledge construction. Multidimensional codifications stimulate the brain and impress meaning to concepts initially empty. Culture is redefined as mosaic-culture, composed by a diversity of media and by immersion in the messages' sphere. In emerge nt countries like Brazil that propose to capacitate citizens for action and for interaction, the aims should imply the respect to the cultural specificities and in the real improvement of the citizens welfare. Information Science in this context must seek theorizations and practices that contribute to social improvements, capacitating and a better understanding of the challenges of Social Web. If the PISA examination demonstrates the County's frailness relating to the information, the 2011 Unicef report point to opportunities. The Universities have an essential role in the capacitating and in the creation of professional contingents, developing their own potentialities in the study, research and knowledge production for a better use of the Information and Communication Technologies. The man-machinery interfaces offer new problems to be dealt together with the literacy lags in Brazil: if information needs to be communicated to re-elaborate in knowledge, its representational supports need to be learnt as technological processes. Implementing informational ambiences studies will produce material for analyses, for the understanding and for the cultural practices importation, converting them to the contextualization of the Country's needs.
Impact of information technology and communication: digital culture and socio-cultural changes
Keywords: Culture; Information Technologies; Knowledge; Social Web